Experimental study of cement-based materials under sulfate attack environment using Electrochemical Impedance Spectroscopy - Niu, Shiwei; Luo, Jin; Chen, MengTing; Chen, Zhiwei; Wang, Xingyi; Bai, Xiangling; Li, Jindu (International journal of electrochemical science, 2023)
In this paper, electrochemical impedance spectroscopy tests and compressive strength tests were employed to investigate the sulfate attack process of cement-based materials, and the change law of the electrochemical impedance spectrum with erosion time was analyzed. Based on the typical equivalent circuit model of cement-based materials and its microstructure equivalent circuit model, the change law of electrochemical parameters and its relationship with compressive strength were analyzed. The experimental results indicate that with increasing erosion time, the electrochemical impedance spectrum shows significant quasi-Randles characteristics, its position moves to the right, and the diameter of the high-frequency semicircle increases. The values of RCP, reflecting disconnected pores, and RCCP, reflecting connected pores, increase continuously during the attack process. The compressive strength of cement-based materials reaches a maximum at a sulfate concentration of 55 g/L. The electrochemical parameter RCCP well reflects the compressive strength of cement-based materials and further characterizes the deterioration of its macro properties.